Pregnancy related risk perception in pregnant women, midwives & doctors: a cross-sectional survey - Suzanne Lee; Des Holden; Rebecca Webb; Susan Ayers (BMC, 2019)
Abstract Background Risk perception in relation to pregnancy and birth is a complex process influenced by multiple personal, psychological and societal factors. Traditionally, the risk perception of healthcare professionals has been presented as more objective and authoritative than that of pregnant women. Doctors have been presented as more concerned with biomedical risk than midwives. Such dichotomies oversimplify and obscure the complexity of the process. This study examines pregnancy-related risk perception in women and healthcare professionals, and what women and professionals believe about each other's risk perception. Methods A cross sectional survey of set in UK maternity services. Participants were doctors working in obstetrics (N = 53), midwives (N = 59), pregnant women (N = 68). Participants were recruited in person from two hospitals. Doctors were also recruited online. Participants completed a questionnaire measuring the degree of perceived risk in various childbirth-related scenarios; and the extent to which they believed others agreed with them about the degree of risk generally involved in childbirth. Main outcome measures were the degree of risk perceived to the mother in baby in pregnancy scenarios, and beliefs about own perception of risk in comparison to their own group and other groups. Results There were significant differences in total risk scores between pregnant women, doctors and midwives in perception of risk to the mother in 68/80 scenarios. Doctors most frequently rated risks lowest. Total scores for perceived risk to the baby were not significantly different. There was substantial variation within each group. There was more agreement on the ranking of scenarios according to risk. Each group believed doctors perceived most risk whereas actually doctors most frequently rated risks lowest. Each group incorrectly believed their peers rated risk similarly to themselves. Conclusions Individuals cannot assume others share their perception of risk or that they make correct assessments regarding others' risk perception. Further research should consider what factors are taken into account when making risk assessments,